PEMETAAN INTENSITAS POLUSI PADA ISOLATOR JARINGAN TRANSMISI - Amali, Lanto Mohamad Kamil (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2011)
The problem in this study were: (1) how the intensity of pollution sector in the region polluted insulator, (2) how polluted insulator surface conductivity Parent substations in each region, (3) how to profile an appropriate insulators for substations with different levels of intensity of pollution sector in the region. To solve this problem pollutant sampling conducted on ceramic insulators on the channel milestone substation switchyard each region at two different points, namely at the top of the insulator and the bottom fin insulators. The results showed the intensity of pollution for every region of substation at a concentration of 0.50 g / l has a value of ESDD with dissolved heavy pollutant levels (> 0.1 mg/cm2), while the value of NSDD categorized insoluble low-level pollutants. Maximum leakage current value obtained by GI. Makale 4.73 mA, GI. Sungguminasa 4.47 mA, GI. Tello 4.60 mA, GI. Long Tallo 4.67 mA and GI. Pangkep 4.87 mA. Â  Keywords : Insulator, Pollutan, ESDD, NSDD